2019
DOI: 10.1002/cssc.201802437
|View full text |Cite
|
Sign up to set email alerts
|

Porous Mn‐Doped FeP/Co3(PO4)2 Nanosheets as Efficient Electrocatalysts for Overall Water Splitting in a Wide pH Range

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…As a consequence, P sites act as proton-acceptor sites and metal sites act as hydride-acceptor sites, leading to high activity of NiCoP for hydrogen evolution process [24]. Recent works [51,52] have demonstrated that PO 4 3À species are beneficial for facilitating water molecule adsorption and promoting oxidation of metal ions for the proton coupled electron transfer procedure. Therefore, the PO 4 3À species on the surface can promote the HER process.…”
Section: àmentioning
confidence: 99%
“…As a consequence, P sites act as proton-acceptor sites and metal sites act as hydride-acceptor sites, leading to high activity of NiCoP for hydrogen evolution process [24]. Recent works [51,52] have demonstrated that PO 4 3À species are beneficial for facilitating water molecule adsorption and promoting oxidation of metal ions for the proton coupled electron transfer procedure. Therefore, the PO 4 3À species on the surface can promote the HER process.…”
Section: àmentioning
confidence: 99%
“…As shown in Figure S16b, the Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF couple delivers the current densities of 10 and 50 mA ⋅ cm −2 at the potentials of 1.54 and 1.76 V in 1 M KOH solution, respectively. Moreover, Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF couple requires a low potential of 1.64 V to afford 10 mA ⋅ cm −2 in 1 M PBS (Figure 4e), which is obviously lower than a string of recently reported neutral‐pH electrocatalysts (Figure 4f) [34–44] . Moreover, Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF shows good stability for water electrolysis under alkaline condition and neutral‐pH water (Figure S14, S15).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, Ir 3 À Ni(OH) 2 /NF k Ir 3 À Ni(OH) 2 /NF couple requires a low potential of 1.64 V to afford 10 mA • cm À 2 in 1 M PBS (Figure 4e), which is obviously lower than a string of recently reported neutral-pH electrocatalysts (Figure 4f). [34][35][36][37][38][39][40][41][42][43][44] Moreover, Ir 3 À Ni(OH) 2 /NF k Ir 3 À Ni(OH) 2 /NF shows good stability for water electrolysis under alkaline condition and neutral-pH water ( Figure S14, S15).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the Tafel slope calculation methods, j o is an additional activity parameter of an electrocatalyst. It illustrates the reaction rate at equilibrium potential and displays the ability of catalysts to transport electrons [94] . Highly active catalysts with larger j o can drive electrochemical reaction with only a small j.…”
Section: An Overview Of Hzor Electrocatalysts: From Noble Metals To Nimentioning
confidence: 99%